Study of maillard reactions with coupled chromatographic and spectroscopic techniques - Ioannou, Aristodimos (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
The present research work was aimed to study model Maillard reactions by a combination of analytical techniques such as HPLC, UV-vis and ATR-FTIR spectroscopies. The Maillard reaction involves a complex network of chemical reactions that occur in food after processing at high temperatures. A further purpose of this study was to develop simple spectroscopic methods of application of the spectroscopic properties of the food constituents. The reaction of asparagine and fructose at high temperature was studied by the coupling technique of HPLC-ATR-FTIR. The coupling of high performance liquid chromatography (HPLC) with FTIR detection provides a further capability for confirming chemical system changes in a new experimental layout. Furthermore, the formation of the Amadori products was identified by employing a combined analytical technique of Solid Phase Extraction (SPE) and Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy (ATR-FTIR). The isolation of reaction products of asparagine with reducing sugars at alkaline pH and high temperature was probed by a combination of high performance liquid chromatography (HPLC) coupled with a Fraction Collector. The reaction products were analyzed by UV-vis and Fourier transform infrared (FTIR) spectrophotometry. The UV- vis and FTIR spectra of the isolated Maillard reaction products showed structure sensitive changes as depicted by deamination events and formation of asparagine saccharide conjugates. Evidence for Cu (II) metal ion complexation with the Maillard reaction products is supported by UV-Vis and FTIR spectroscopy. The same model system was utilized to investigate the interaction of Maillard reaction products formed by the reactions of saccharide-derived compounds creating intermediates with proteins, more specifically with hemoglobin and myoglobin. The spectral events upon addition of discrete MRPs to hemoglobin and myoglobin were monitored. This led to the formation of a modified protein adduct known as a hemichrome. Additionally, fluorescence spectroscopy was employed as a complementary technique to study the reaction of hemoglobin with MRPs from an asparagine-sugar model system. The modification of hemoglobin by MRPs was illustrated through tryptophan- specific changes in the fluorescent spectra.
Keywords: Model; Maillard reactions; Asparagine; Fructose; High temperature